AN INDIVIDUAL’S AESTHETIC ORIENTATION AND ITS CONNECTION WITH THE EMPATHY - Kechur, Roman; Yaskevych, Olha; Turezka, Khrystyna (PSYCHOLOGICAL JOURNAL, 2020)
The question of aesthetic experience is at the center of this study and is derived out of the concepts of art perception and experiencing. Here, aesthetics is understood not so much as the value sphere of Super-Ego, but rather as a style of mental activity of Ego, which is determined primarily by a peculiar way of personalized cognition based on empathy. We assume that empathy allows for an aesthetic approach to reality in general. And vice versa, an aesthetic process is possible only to the extent that a person is empathetic, that is, able to use empathy as a mode of perception. Therefore, the empathy of young people with a distinct aesthetic orientation was empirically investigated. These respondents were compared with those who had ethical orientation. The obtained results revealed two different mechanisms of empathy - emotional resonance and cognitive reflection – characteristic for the both studied groups. Thus, these mechanisms were more complementary than alternative; and the limitations of correct cognition of (interpersonal) reality in both cases are revealed. Aesthetically-oriented people tend to rely on intuition; they trust their sensuality and are emotionally open, following their impressions and first emotional reactions. At the same time, they may lack the observing Ego, preferring feeling instead of thinking, so they are managed rather by pleasure principle, and they can use art practices in order to compensate frustrations and isolate themselves from the demanding reality. The study also highlights the distinctive features of ethically-oriented young people, most notably, their excessive self-distancing, a lack of confidence in intuitive assessments, and a tendency to rely on abstract rules instead of following “here and now” feelings and personal (situational) ethics. The difference between empathetic perception of aesthetically and ethically oriented people is investigated and described in terms of intuitive and cognitive empathy. Each mode of empathy has its significant limitations, if it dominates the other. Therefore, it is assumed that a mature position lies precisely in the balance of aesthetic and ethical attitudes towards the (interpersonal) reality.